Democratic Republic of Sao Tome and Principe : First Review Under the Three Year Arrangement Under the Extended Credit Facility Arrangement, and Request for Waivers of Performance Criteria; Staff Report; Staff Supplement; and Press Release on the Executive Board Discussion. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
This paper presents the Democratic Republic of Sao Tome and Principe's first review under the Three Year Arrangement under the Extended Credit Facility Arrangement. After averaging 6 percent a year over several years, real GDP growth in 2009 is estimated at 4 percent, reflecting a decline in foreign direct investment (FDI), which in part reflected the impact of the global crisis. Growth is expected to rebound in 2010, based on new FDI and increased official external financing.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet